THE ROLE OF NOTICING IN DEVELOPING SPEAKING SKILLS - Teshaboyeva Nafisa Zubaydulla qizi Scientific advisor: Jizzakh branch of the National university of Uzbekistan named after Mirzo Ulug’bek. The faculty of psychology, the department of Foreign languages; Philology; teaching languages: English Musurmonov (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
Speaking is one of the most essential skills in learning a foreign language. Among many factors that help students become fluent speakers, one important element is noticing. Noticing means paying attention to how language is used by others and how one uses it themselves. This article explains how noticing works, why it is important for developing speaking skills, and how it can be used in classroom practice. Practical examples are given to show how both teachers and students can benefit from noticing activities.